Early Christian families in context an interdisciplinary dialogue - Balch, David L.; Osiek, Carolyn (Grand Rapids, MI Eerdmans, 2003)
Includes bibliographical references and indexes.
Keywords: Family -- religious aspects -- Christianity -- history -- congresses; Family -- ancient Rome -- congresses